Kajian Ulang Perencanaan Geometrik Simpang Simpang Tak Bersinyal Berdasarkan Highway Capacity Manual - Tripoli, Bambang; Febrianti, Dian; Mawardi, Edi; Zulyaden, Zulyaden; Supriadi, Supriadi (Tameh, 2021)
Simpang Empat Jeuram Nagan Raya is often mentioned by local people as “Simpang Peut” is the main route of the city's arterial road serving traffic movement between districts or between provinces, which is located in Kuala District, Nagan Raya Regency. The intersection has four arms, serving the flow of 4 lanes of the main road with a median and 2 lanes of minor roads connecting the route for offices, residential residents, trade and as a route to the city center. The problem that is raised and also the purpose of research is how the performance of the intersection to traffic volume occurs in the four arms and distinguishes the difference between the current calculation and previous research. The limitations of the discussion are the research location at Simpang Empat Jeuram, the performance of the intersection based on the 1993 HCM method, side barriers and not predicting previous research. Based on the results, the current volume is 3,310 pcu/hour with a composition of 2,789 pcu/hour. The capacity of 4,009 pcu/hour is above the existing volume which is categorized as not jammed or not saturated. Side barriers 1,328 events are categorized as commercial areas and roadside market activity is very high. The degree of saturation is 0.70 < DS (DS < 0.80 - 0.90) with an average delay of 7.95 seconds/pcu and a queue length of 40% - 20% with a service level D where the current is unstable and sometimes has to slow down the speed of 43 km/hour. Previous research has shown significant results, because the increase in vehicles has continued to increase by 75% in the last 3 years.